2011
DOI: 10.1002/jmr.1096
|View full text |Cite
|
Sign up to set email alerts
|

Structural, thermodynamic, and kinetic basis for the activities of some nucleic acid repair enzymes

Abstract: X-ray structural analysis provides no quantitative estimate of the relative contribution of specific and nonspecific or strong and weak interactions to the total affinity of enzymes for nucleic acids. We have shown that the interaction between enzymes and long nucleic acids at the molecular level can be successfully analyzed by the method of stepwise increase in ligand complexity (SILC). In the present review we summarize our studies of human uracil DNA glycosylase and apurinic/apyrimidinic endonuclease, E. co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
121
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(127 citation statements)
references
References 109 publications
0
121
0
Order By: Relevance
“…Up to the present time using SILC approach, only regularities of DNA recognition by different enzyme were investigated. Usually the linear log‐dependencies for d(pN) n oligonucleotides (for 0 ≤ n ≤ 10–20, n = 0 corresponds to ortho phosphate) provide evidence of the additivity of ΔG o values for the interaction dependently of enzyme of 7 to 20 individual nucleotide units of d(pN) n with DNA‐binding sites of many enzymes analyzed (see references above, reviewed in the previous studies). Only dependencies −log( K d ) upon n in the case of HIV‐1 integrase showed 2 close to linear regions at n = 0 to 2 and n = 4 to 20 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Up to the present time using SILC approach, only regularities of DNA recognition by different enzyme were investigated. Usually the linear log‐dependencies for d(pN) n oligonucleotides (for 0 ≤ n ≤ 10–20, n = 0 corresponds to ortho phosphate) provide evidence of the additivity of ΔG o values for the interaction dependently of enzyme of 7 to 20 individual nucleotide units of d(pN) n with DNA‐binding sites of many enzymes analyzed (see references above, reviewed in the previous studies). Only dependencies −log( K d ) upon n in the case of HIV‐1 integrase showed 2 close to linear regions at n = 0 to 2 and n = 4 to 20 …”
Section: Resultsmentioning
confidence: 99%
“…However, static structures of the complexes cannot provide quantitative estimates of the relative importance of individual contacts as well as the relative contributions of weak and strong nonspecific and specific contacts to the total affinity of enzymes for proteins, peptides, DNA, and oligonucleotides. To evaluate the relative contributions of individual DNA elements to the enzyme affinity for long polymeric and oligomeric ligands, a new approach, stepwise increase in ligand complexity (SILC), was developed . Using the SILC, we have analyzed the mechanisms of recognition of DNA by number of DNA‐dependent enzymes: not specific for DNA sequence and structure such as Escherichia coli RecA, specific for DNA structure but not sequence‐dependent such as DNA polymerases of eukaryotes, prokaryotes, viruses, and archaea and human DNA ligase I; specific for DNA containing damages such as human uracil DNA glycosylase, E. coli Fpg and human 8‐oxoguanine DNA glycosylases (OGG1), human apurinic/apyrimidinic endonuclease (AP endonuclease), as well as specific for DNA sequence such as human HIV integrase, topoisomerase I (Topo I), Eco RI restriction endonuclease, and human lactoferrin (LF) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As hydroxyl radical footprinting requires that the protein–DNA complex show either increased or decreased reactivity, it is expected that this approach often underestimates the full extent of protein–DNA interactions. APE1 interaction with single-strand and duplex DNA was previously characterized by comparing the inhibition of different length oligonucleotides (34,35). Experiments with blunt-ended oligonucleotides concluded that APE1 can bind favourably to 10 bp of duplex DNA (35), which is similar to our results with hairpin DNA.…”
Section: Discussionmentioning
confidence: 99%